New technologies in the financial industry: case of Poland - Iwanicz-Drozdowska , Małgorzata; Cichowicz, Ewa; Cicirko, Marianna; Kawiński , Marcin; Nowak, Agnieszka K. (Economics and Business Review, 2023)
This study evaluates the scope and consequences of the application of new technologies (NTs) within the Polish banking and insurance sectors and thus contributes to the knowledge of  CEE financial market development. The goal is to understand the implementation of particular NTs in two different sectors and identify the motivations, strategies, phases of realisation and cost efficiency depending on the institution’s size. The detail of the study requires the use of qualitative research methods. In-depth interviews are employed to figure out the criteria based on which decisions to implement NTs are made. The findings indicate that the primary objective of NT implementation is to respond to customers’ needs, followed by cost-cutting and achieving more efficient internal processes. The application of artificial intelligence (AI) and machine learning (ML) in risk management areas is still a work in progress. In the next five  years  cloud computing is expected to become the most important NT and  thus  will have to meet numerous regulatory requirements.